The glocal curriculum: A model for transnational collaboration in higher education for sustainable development. (10th January 2018) - Caniglia, Guido; John, Beatrice; Bellina, Leonie; Lang, Daniel J.; Wiek, Arnim; Cohmer, Sean; Laubichler, Manfred D.
Abstract: Transnational collaborations between universities provide an underutilized opportunity to teach sustainability competencies emphasizing the global and local nature of (un)sustainability. This article asks: what kind of curricula and teaching-learning environments can we use in transnational collaborations so as to prepare future generations to address (un)sustainability across different scales and contexts? The article presents a glocal model for transnational collaboration for sustainability which combines the use of digital technologies for global collaboration with experiences and engagement for local learning and impact. The glocal model was designed and implemented in The Global Classroom, a collaborative project between Arizona State University and Leuphana University of Lüneburg. The model fills two important gaps in higher education for sustainable development. In the theory, it provides new concepts to think about the curriculum and teaching-learning environment of transnational collaborations for sustainability. In the practice, it presents an exemplary implementation that can inform the curriculum as well as the teaching-learning environment of such collaborations. The article concludes that transnational collaborations for sustainability ought to more systematically integrate curriculum reform with approaches to internationalization and digitalization of higher education.